Republic of Uzbekistan : Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2005)
This paper reviews Uzbekistan's Interim Welfare Improvement Strategy Paper (I-WISP). I-WISP defines the main directions and measures aimed at improving living standards and reducing poverty among the population of Uzbekistan for 2005-10. The strategy is designed to further expand reforms in all aspects of life in the society based on the national model of economic and social development, the social values of the people of Uzbekistan, and their commitment to the processes of integration into the world community.